Controlling Microbial Safety Challenges of Meat Using High Voltage Atmospheric Cold Plasma - Han, Lu; Ziuzina, Dana; Heslin, Caitlin; Boehm, Daniela; Patange, Apurva; Sango, David M.; Valdramidis, Vasilis P.; Cullen, Patrick J.; Bourke, Paula (Frontiers in Microbiology, 2016)
Atmospheric cold plasma (ACP) is a non-thermal technology, effective against a wide range of pathogenic microorganisms. Inactivation efficacy results from plasma generated reactive species. These may interact with any organic components in a test matrix including the target microorganism, thus food components may exert a protective effect against the antimicrobial mode of action. The effect of an in-package high voltage ACP process applied in conjunction with common meat processing MAP gas compositions as well as bacteria type and meat model media composition have been investigated to determine the applicability of this technology for decontamination of safety challenges associated with meat products. E. coli, L. monocytogenes and S. aureus in PBS were undetectable after 60 s of treatment at 80 kVRMS in air, while ACP treatment of the contaminated meat model required post treatment refrigeration to retain antimicrobial effect. The nutritive components in the meat model exerted a protective effect during treatment, where 300 s ACP exposure yielded a maximum reduction of 1.5 log using a high oxygen atmosphere, whilst using air and high nitrogen atmospheres yielded lower antimicrobial efficacy. Furthermore, an ROS assay was performed to understand the protective effects observed using the meat model. This revealed that nutritive components inhibited penetration of ROS into bacterial cells. This knowledge can assist the optimization of meat decontamination using ACP technology where interactions with all components of the food matrix require evaluation.